Hydrops fetalis associated with chorioangioma and thrombosis of umbilical vein - Sivasli, Ercan; Tekşam, Ozlem; Haliloğlu, Mithat; Güçer, Safak; Orhan, Diclehan; Gürgey, Aytemiz; Tekinalp, Gülsevin (The Turkish Journal of Pediatrics, 2009)
Placental chorioangioma and thrombosis of an umbilical vein varix are rare etiologic factors of non-immune hydrops fetalis. Herein, we report a patient who had hydrops fetalis associated with placental chorioangioma and thrombosis of an umbilical vein varix. This is the first report of coexistence of non-immune hydrops fetalis with placental chorioangioma and thrombosis of an umbilical vein varix.